Konsep Kepemilikan Hak Atas Merek di Indonesia (Studi Pergeseran Sistem "Deklaratif"ke dalam Sistem "Konstitutif") - R. Murjiyanto (Jurnal Hukum IUS QUIA IUSTUM, 2017)
This research is designed to study a number of issues including first, what becoming the philosophical base of consideration in the displacement in the brand registration from the declarative system (first to Use) into the system. Constitutive (First to File)? Second, Why the occurrence of equal brand between one and other parties still exist? Third how does the model of implementation of Constitutive System in the brand registry give the just legal security? This research concluded first, the replacement of the declarative system (First to Use) into the Constitutive System (First to File) in the management of brand in Indonesia is based upon the consideration to reach the legal objective particularly for guaranteeing the legal security and justice in the right protection for the brand owner. Second, the occurrence of registration of equal brand, even the one with good reputation, commonly is based upon a bad intention of the registrants prioritizing their own interest for profit by using the fame. Third, the implementation of Constitutive System or “First to File” in brand registration to give a just legal security that is by applying the constitutive system or “First to File” tightly and consistently in which the rights and protection to the brand are only given the registered brand owner and any claim of cancelation can only be done by the registered brand owner.